A new approach to extract reference currents for multilevel shunt active filter in three phase systems - Abdelkader Yousfi; Tayeb Allaoui; Abdelkader Chaker (Institute of Advanced Engineering and Science, 2020)
In this article, we present a new study of technique to extract reference currents for three-level shunt active filter controlling by fuzzy logic. The APFs is realized using three phase voltage and the carrier-based PWM strategy. A new technique for identifying reference currents will be developed. It is based on concordia method using multi-variable filter, and makes the total or selective extraction harmonic currents of references, and by consequence making their compensations, total or selective. The results of digital simulation in the Matlab-Simulink environment of a system of power to thyristor outputs on an inductive load show well the effectiveness of this new technique of extraction of the harmonics of reference.